2018
DOI: 10.31279/2222-9345-2018-7-31-55-59
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Productive Longevity of Black-and-Motley Breed Cows With Tethered and Unbonded Methods of Keeping

Abstract: Период продуктивного долголетия коров является одним из основных показателей, характеризующих эффективность производственного процесса на молочном предприятии. Известно, что интенсивное использование животных (в том числе и на высокотехнологичных доильных установках) приводит к сокращению срока производственного использования животных. Исследования проводили на базе ЗАО «Агрофирма «Патруши» Сысертского района Свердловской области, где коров доят в доильном зале с применением установки «Европараллель», содержан… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Numerous diseases can therefore develop during pregnancy and disrupt the development of the fetus. Some researchers believe (Avdeenko et al 2016;Chechenikhina and Loretz 2018) that the observed disturbances in reproductive function of cows with enhanced genetic potential for dairy productivity are associated mainly with significant and inadequate changes in metabolism. Consequently, the way to solve the problem of gestosis in high-producing dairy cattle at the end of pregnancy is to study the role of metabolic disorders that facilitate the development of subclinical ketosis and gestosis in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous diseases can therefore develop during pregnancy and disrupt the development of the fetus. Some researchers believe (Avdeenko et al 2016;Chechenikhina and Loretz 2018) that the observed disturbances in reproductive function of cows with enhanced genetic potential for dairy productivity are associated mainly with significant and inadequate changes in metabolism. Consequently, the way to solve the problem of gestosis in high-producing dairy cattle at the end of pregnancy is to study the role of metabolic disorders that facilitate the development of subclinical ketosis and gestosis in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%